Fundamentals of resistance training: Progression and exercise prescription - Kraemer, W. J.; Ratamess, N. A. (Medicine & Science in Sports & Exercise, 2004)
Progression in resistance training is a dynamic process that requires an exercise prescription process, evaluation of training progress, and careful development of target goals. The process starts with the determination of individual needs and training goals. This involves decisions regarding questions as to what muscles must be trained, injury prevention sites, metabolic demands of target training goals, etc. The single workout must then be designed reflecting these targeted program goals including the choice of exercises, order of exercise, amount of rest used between sets and exercises, number of repetitions and sets used for each exercise, and the intensity of each exercise. For progression, these variables must then be varied over time and the exercise prescription altered to maintain or advance specific training goals and to avoid overtraining. A careful system of goal targeting, exercise testing, proper exercise technique, supervision, and optimal exercise prescription all contribute to the successful implementation of a resistance training program.